(3GdTeSjI GdefUhQjIs - (3MSf Hf fhM GdbeQj, CHh efUhQ,fMh (B380 (3g`s ((3KeGf GdchjJi ? s)
(3ChdgG (B:s
(3bGd CHh efUhQ , GdMSf Hf fhM GdbeQi Efi de CRd ai UHGi efP YbdJ , CMH GdYdhe s
(3BNQgG (B:s
(3hJbhjI ai BNQgG GdCeQ Ef MUd ajg GdJMdjd hGdESJaQGZ ZjQ GdCOhjI hHOdgG aEf ajgG eGgh CfaY s
(3fSNI CNQis
(3eUOQ HagQS JaUjdi dCHhGH GdebGdGJ hHBNQgG JbQjX dCejf LdHis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B299s
Keywords: (3GdWHs